2013
DOI: 10.4103/2230-8598.109320
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health status and care practices among children of female workers in unorganized sector

Abstract: Aims:To assess the health of children of construction workers with the help of anthropometric measurements and to explore their childcare practices. Settings and Design: Female construction workers and their children of age 12 to 36 months were taken as one study unit. The study had two components. One component deals with anthropometric measurements of the children while a qualitative descriptive exploratory component was used to explore mothers' perspectives and childcare practices. Methodology: Anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There may be many explanations for this finding. A study including female construction workers in India identified fear of wage loss due to decreased productivity as a primary obstacle in attending to a child’s needs when accompanying mother to work [24]. In other words, even when a mother or other caregiver is permitted to bring her child to work, she may feel pressure to neglect a child’s nutritional needs in order to maintain employment and provide financially for her family.…”
Section: Discussionmentioning
confidence: 99%
“…There may be many explanations for this finding. A study including female construction workers in India identified fear of wage loss due to decreased productivity as a primary obstacle in attending to a child’s needs when accompanying mother to work [24]. In other words, even when a mother or other caregiver is permitted to bring her child to work, she may feel pressure to neglect a child’s nutritional needs in order to maintain employment and provide financially for her family.…”
Section: Discussionmentioning
confidence: 99%
“…In the study done by Nayak approximately one third of children were exclusively breast fed for 6 month or more, 34.7% were given prelacteal feed and most common feed was sugar water; while in study conducted by Chawada et al in 67 children of <36 months age only 11% could practice exclusive breast-feeding for 6 months. 13,14…”
Section: Initiation Of Breast Feeding (In Hours)mentioning
confidence: 99%